Information structure in spoken Japanese - Nakagawa, Natsuko (Language Science Press, 2021)
This study explores information structure (IS) within the framework of corpus linguistics and functional linguistics. As a case study, it investigates IS phenomena in spoken Japanese: particles including so-called topic particles, case particles, and zero particles; word order; and intonation. The study discusses how these phenomena are related to cognitive and communicative mechanisms of humans.